Becoming empowered: A study of counsellor development - Donald Sawatzky, D.; Jevne, Ronna F.; Clark, Graeme T. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study was designed to explore the question of what experiences contribute to the development of effectiveness as a counsellor. A qualitative research methodology was utilized in which doctoral students from one program in counselling psychology were interviewed. Based on a thematic analysis of the interviews, a cyclical model of counsellor development is proposed. The overall process has been named "Becoming Empowered" which includes recurring themes identified as: experiencing dissonance, responding to dissonance, relating to supervision and feeling empowered. Several implications of this research are highlighted.